الفرق بين الصفة والمصلحة في الدعوى الإدارية - الزهراني، عبدالغني بن درباش بن موسى (عبدالفتاح محمود ادريس, 2023)
تناول هذا البحث موضوعا من المواضيع القضائية والمتعلقة بالمرافعات بوجه التحديد، وقد اختار طريق المرافعات الإدارية لندرة الكتابة فيها، ووجود بعض الإشكالات التي تحتاج إلى بحث وتمحيص، ووقع الاختيار على موضوع الصفة والمصلحة؛ باعتبارهما موضوعان ومصطلحان يكثر الخلط بينهما، وكذلك التداخل بينهم، إذ إن المصلحة والصفة في الدعوى الإدارية تختلف من دعوى الإلغاء عن غيرها من الدعاوى الإدارية، كما أن جل من كتب فيها قد أظهر مواطن اللبس والخلل، وارتكز البحث على بيان أوجه الاتفاق والاختلاف بينهما وأنواعهما من حيث الشكل والموضوع، وكذلك من حيث التعلق بالأدبية والمادية، وخلص البحث إلى النتائج المرجوة منه وذلك بوضع معالم وحدود للفوارق بين المصلحة والصفة حتى لا يقع اللبس والخلط بينهما، واعتمد البحث في ذلك على العديد من المراجع، ومنها الخاصة بالقضاء الإداري، وموضوعات الصفة والمصلحة. This research dealt specifically with judicial and pleadings topics. It chose the course of administrative arguments for the paucity of writing, the existence of some problems requiring research and scrutiny, and the choice of the subject of quality and interest; As two subjects and two terms that are frequently confused, as well as overlapping between them, since the interest and quality of the administrative action differs from that of annulment to other administrative proceedings, And most of those who wrote in it have shown a citizen of confusion and imbalance, The research was based on an indication of the agreement and differences between them and their types of form and subject matter. As well as in terms of moral and material attachment, the research concluded the desired results by establishing milestones and limits of differences between interest and quality so as not to be confused. The research relied on numerous references, including on administrative justice, and topics of capacity and interest.
Keywords: الدعاوى الإدارية -- شروط المصلحة -- شروط الصفة -- الأحكام الفقهية